2016
DOI: 10.1016/j.jssr.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Who are we? The Demographic and Professional Identity of Social Studies Teacher Educators

Abstract: Growth in racial and ethnic diversity among public school P-12 students stands in stark contrast to the teaching population who tend to be monolingual, White females. Secondary social studies teachers defy demographic teacher trends, as they tend to be male, albeit White males who still are not representative of the students they teach. What is missing from the discourse of student–teacher imbalance however is discussion surrounding diversity among social studies teacher educators. The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Darling-Hammond, Holtzman, Gatlin, and Vasquez Heilig (2005) mentioned the disparity between representation of students and teachers in their study about teacher preparation and teacher demographics. Their work exemplifies the problem that Busey and Waters (2016) and Bower-Phipps, Homa, Albaladejo, Johnson, and Cruz (2013) discussed the changing demographics of classrooms while teachers and teacher preparation programs remain mostly White. Their research represented one of the continuous issues with how teachers come into the field and how they become teachers.…”
Section: Research About Latinx Teachersmentioning
confidence: 86%
See 1 more Smart Citation
“…Darling-Hammond, Holtzman, Gatlin, and Vasquez Heilig (2005) mentioned the disparity between representation of students and teachers in their study about teacher preparation and teacher demographics. Their work exemplifies the problem that Busey and Waters (2016) and Bower-Phipps, Homa, Albaladejo, Johnson, and Cruz (2013) discussed the changing demographics of classrooms while teachers and teacher preparation programs remain mostly White. Their research represented one of the continuous issues with how teachers come into the field and how they become teachers.…”
Section: Research About Latinx Teachersmentioning
confidence: 86%
“…As the classroom and the nation become more black, brown, and yellow, the teachers who run and administer these classrooms remain White (Bower-Phipps, Homa, Albaladejo, Johnson, & Cruz, 2013;Busey & Waters, 2016;United States Census Bureau, 2010). There are hopes that the population of teachers will also reflect these changing demographics.…”
Section: Introductionmentioning
confidence: 99%
“…Social studies departments were predominantly male as were teacher-coaches in each school (A. Brown, 2012a;Busey & Waters, 2016;A. Brown & Sieben, 2013;Chiodo et al, 2002;Fitchett, 2010;Weller, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have routinely suggested that providing students with opportunities to engage with controversial issues in social studies classrooms contributes to building conceptions of lived democracy and democratic citizenship (Parker, 2003;Ross and Marker, 2005;Engle and Ochoa, 1988;Hess, 2011). In a recent examination of social studies teacher educators, Busey and Waters (2016) identified several "critical areas" for research in social studies education, including race/critical race theory, democratic and citizenship education and social justice (p. 80). However, looking to the research on teaching social issues, findings indicate that classroom discussions are infrequent, and when offered are typically brief (Kahne and Middaugh, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%